Bottling, Labeling, and Selling Honey in Florida - Amy T. Vu; Jennifer Hagen; Nancy Gentry; James D, Ellis; Mary Bammer (EDIS, 2022)
The intended audience is Florida beekeepers of all operation sizes from small scale to commercial. There are 5,000 registered beekeepers in the state, managing almost 700,000 colonies. The Florida Department of Agriculture and Consumer Services have updated their rules and regulations related to honey production and what falls under the "Cottage Food Law." This publication provides beekeepers with Florida’s updates, so they will be able to sell honey legally under this law.